Performance of Improved Varieties of Pulse Crops at Farmers’ Field in Kymore Plateau and Satpura Hills Zone of Madhya Pradesh (Indian Journal of Extension Education, 2017)
The Panna district falls under Kymore plateau and Satpura hills agro climatic zone of Madhya Pradesh. This zone occupies the major pulse producing regions of the state, however recording the low productivity as compared to yield potential of the crops. Majority of the farmers in this region were still cultivating the traditional old varieties along with higher seed rate which causes reduced production as well as higher cost of production. Under such circumstances the frontline demonstration (FLD) is an appropriate tool for the introduction and dissemination of improved varieties of pulse crops. In view of this performance of improved varieties of pulse crops viz. Chickpea (JG-11, JG 16 and Vijay), Lentil (JL-3), Pigeonpea (JKM-189 and TJT-501) and Black gram (PU-35) were assessed through front line demonstration during 2010-11 to 2013-14 in Panna district. The result on the performance of improved varieties of Chickpea, Lentil, Pigeonpea and Black gram, respectively increased the average yield by 40.4 percent, 60.0 percent, 40.0 percent and 55.0 percent over local existing varieties of the pulse crops. Higher yield of the improved varieties of the pulse crops facilitate and boost up the farmers to start seed production of the concerned varieties that brought out a significant achievement in the adoption of the improved varieties. It has been observed that the technology gap for all the crops is higher than the extension gap which indicates that there is scope to a great extent to improve the level of conducted FLDs. In addition, the technology index was also higher which express that there is need to educate the farmers for rapid adoption of improved varieties of pulse crops in this agro climatic zone.